Additional structured physical activity does not improve walking in older people (> 60 years) undergoing inpatient rehabilitation: a randomised trial - Said, C.; Morris, M.; McGinley, J.; Szoeke, C.; Workman, B.; Liew, D.; Hill, Keith; Woodward, M.; Wittwer, J.; Churilov, L.; Danoudis, M.; Bernhardt, J. (Australian Physiotherapy Association, 2018)
Questions: Among older people receiving inpatient rehabilitation, does additional supervised physical activity lead to faster self-selected gait speed at discharge? Does additional supervised physical activity lead to better mobility, function and quality of life at discharge and 6 months following discharge? Design: Multi-centre, parallel-group, randomised controlled trial with concealed allocation, assessor blinding, and intention-to-treat analysis. Participants: Older people (age > 60 years) from two Australian hospitals undergoing rehabilitation to improve mobility. Intervention: Participants received multidisciplinary care, including physiotherapy. During hospital rehabilitation, the experimental group (n = 99) spent additional time daily performing physical activities that emphasised upright mobility tasks; the control group (n = 99) spent equal time participating in social activities. Outcome measures: Self-selected gait speed was the primary outcome at discharge and a secondary outcome at the 6-month follow-up. Timed Up and Go, De Morton Mobility Index, Functional Independence Measure and quality of life were secondary outcomes at discharge and tertiary outcomes at the 6-month follow-up. Results: The experimental group received a median of 20 additional minutes per day (IQR 15.0 to 22.5) of upright activities for a median of 16.5 days (IQR 10.0 to 25.0). Gait speed did not differ between groups at discharge. Mean gait speed was 0.51 m/s (SD 0.29) in the experimental group and 0.56 m/s (SD 0.28) in the control group (effect size -0.06 m/s, 95% CI -0.12 to 0.01, p = 0.096). No significant differences were detected in other secondary measures. Conclusion: While substantial gains in mobility were achieved by older people receiving inpatient rehabilitation, additional physical activity sessions did not lead to better walking outcomes at discharge or 6 months. Trial registration: ACTRN12613000884707. [Said CM, Morris ME, McGinley JL, Szoeke C, Workman B, Liew D, Hill KD, Woodward M, Wittwer JE, Churilov L, Danoudis M, Bernhardt J (2018) Additional structured physical activity does not improve walking in older people (> 60 years) undergoing inpatient rehabilitation: a randomised trial. Journal of Physiotherapy 64: 237–244]